Roca, Zoran (ed.) (2013). Second Homes Tourism in Europe. Lifestyle Issues and Policy Reponses - López-Colás, Julián (Documents d’Anàlisi Geogràfica, 2014)
Roca, Zoran (ed.) (2013) Second Homes Tourism in Europe. Lifestyle Issues and Policy Reponses Surrey: Ashgate, 331 p. ISBN 978-1-4094 -5071- 9